The Effect of Hot Seat Strategy on Students' Reading Aloud Skills - Nurul Faddhia; Muhamad Firdaus Bin Alias; Wirdatul Urfa (Journal of Arabic Literature, Teaching and Learning, 2025)
The interactive learning hot seat strategy in which a student sits in the “hot seat” and assumes the role of a character from a text that has been read. Other students then ask questions to the student in the hot seat, who must answer as if they were the character. This study aims to Analyze the process of applying the hot seat strategy in teaching reading aloud as well as Knowing the level of students' reading aloud ability before the application of the hot seat strategy. This study used a quantitative approach with a quasi-experimental method. The research design applied was Nonequivalent Control Group Design, which is a design with unequal control groups. In this design, there are two groups: an experimental group that receives treatment and a control group that does not receive treatment, but the placement of subjects into these groups is not randomized. The results showed students' initial ability in reading aloud before using the hot seat strategy. The implementation of this study shows that, this study is expected to provide new insights in the method of teaching reading aloud, especially in the context of Arabic language education at the secondary school level.